Clinical and Treatment Considerations for the Pediatric and Aging Patients with Multiple Sclerosis - Siddiqui, Areeba; Yang, Jennifer H; Hua, Le H; Graves, Jennifer S (Neurologic clinics, 2024)
Chronologic aging is associated with multiple pathologic and immunologic changes that impact the clinical course of multiple sclerosis (MS). Clinical phenotypes evolve across the lifespan, from a highly inflammatory course in the very young to a predominantly neurodegenerative phenotype in older patients. Thus, unique clinical considerations arise for the diagnosis and management of the two age extremes of pediatric and geriatric MS populations. This review covers epidemiology, diagnosis, and treatment strategies for these populations with nuanced discussions on therapeutic approaches to effectively care for patients living with MS at critical transition points during their lifespan.Chronologic aging is associated with multiple pathologic and immunologic changes that impact the clinical course of multiple sclerosis (MS). Clinical phenotypes evolve across the lifespan, from a highly inflammatory course in the very young to a predominantly neurodegenerative phenotype in older patients. Thus, unique clinical considerations arise for the diagnosis and management of the two age extremes of pediatric and geriatric MS populations. This review covers epidemiology, diagnosis, and treatment strategies for these populations with nuanced discussions on therapeutic approaches to effectively care for patients living with MS at critical transition points during their lifespan.